Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the Analysis of affecting factors in detection the external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external auditor for money laundering external - Al-Husseini, Essam (Opción, 2019)
The study aimed to know affecting factors in detection and reporting of the external auditor for money laundering operations. For the purpose of testing hypotheses, researcher used both inductive and practical methods in order to collect the data and review the previous scientific research related to the subject. Study showed that Iraq’s external financial auditor has knowledge of the importance of auditing the direction of money laundering, and lack of detection of money laundering operations. In conclusion, lack of detection of money-laundering operations that threaten businesses in the eyes of the Iraqi external auditor is indicative of business administration factors.